Phosphoserine/threonine binding domains: molecular integrators of protein kinase signaling in cell cycle control and cancer - Yaffe, Michael (Henry Stewart Talks, 2008)
Protein phosphorylation, Historical perspective on signaling by tyrosine kinases, The human kinome, How can phosphorylation control enzyme activity, The new 'dogma' of signal transduction by serine/threonine kinases, New phospho-binding domains, Polo family kinases together with cyclin-dependent kinases play many roles throughout mitosis, Architecture of polo-like kinases, Structural basis for phospho-dependent binding, What does the polo-box domain do in cells, A proteomic approach to identifying new phospho-Ser/Thr-binding domains, The DNA damage response pathway, BRCA1, Cancer associated mutations